2004
DOI: 10.1095/biolreprod.103.020305
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Regulation of Glycosylation of Golden Hamster (Mesocricetus auratus) Oviductin During the Estrous Cycle1

Abstract: The oviduct contributes to the reproductive environment by secreting various factors, including a family of glycoproteins termed oviductins. Although many studies have demonstrated that ovarian hormones modulate oviductin gene expression in several mammalian species, there has been controversy surrounding the regulation of golden hamster oviductin. The current study was undertaken to investigate the transcriptional and translational modifications of hamster oviductin during the estrous cycle. First, we verifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…At least in ungulates, oviductin increases the ZP's resistance to proteolysis, and this ZP hardening might be of crucial importance to warrant monospermic fertilization or sperm selection. The presence of different isoforms of oviductin and different levels of glycosylation of oviductin has been reported (McBride et al 2004). Studies using recombinant oviductins in different forms would disclose the molecular basis of such physiological differences.…”
Section: Figure 1 (1) Spermatozoa Carry Out Glycodelin S From a Semimentioning
confidence: 99%
“…At least in ungulates, oviductin increases the ZP's resistance to proteolysis, and this ZP hardening might be of crucial importance to warrant monospermic fertilization or sperm selection. The presence of different isoforms of oviductin and different levels of glycosylation of oviductin has been reported (McBride et al 2004). Studies using recombinant oviductins in different forms would disclose the molecular basis of such physiological differences.…”
Section: Figure 1 (1) Spermatozoa Carry Out Glycodelin S From a Semimentioning
confidence: 99%
“…Most of the carbohydrates are present in O‐linked chains but N‐linked chains have also been detected (Malette & Bleau, 1993). Glycosylation differences detected over the oestrous cycle could be responsible for a different biological role of oviductal‐secreted glycoproteins (McBride et al , 2004; McBride Brockhausen, & Kan, 2005). Third, OVGP1 activity could be affected by ZP composition.…”
Section: Pre‐fertilisation Zona Pellucida Hardeningmentioning
confidence: 99%
“…The nucleotide sequence of the haOv m fragment is unique to hamster oviductin and does not resemble any other glycoproteins. The specificity of the affinity-purified anti-haOv m antibody has been established by Western blotting analysis (McBride et al 2004). …”
Section: Polyclonal Antibodymentioning
confidence: 99%
“…Because mammalian oviductins share a common property of being highly glycosylated macromolecules, it has been suggested that different forms of oviductins, varying in number and distribution of oligosaccharide side chains, may be responsible for their diverse biological functions (Buhi 2002). Recently, we have produced a polyclonal antibody against recombinant hamster oviductin that recognizes a peptide portion of hamster oviductin (McBride et al 2004). The newly developed anti-rhaOv m antibody differs from the previously used monoclonal antibodies, which recognize glycosidic epitopes attached to the protein backbone (Araki et al 1987;Kan et al 1988Kan et al ,1989Kan et al ,1993St-Jacques and Bleau 1988;Abe and Oikawa 1990;Martoglio and Kan 1996).…”
mentioning
confidence: 99%